2020
DOI: 10.1007/s00268-020-05560-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Proctectomy for Rectal Cancer: A National Perspective on Short‐term Outcomes and Morbidity

Abstract: Background Prior randomized trials showed comparable short-term outcomes between open and minimally invasive proctectomy (MIP) for rectal cancer. We hypothesize that short-term outcomes for MIP have improved as surgeons have become more experienced with this technique. Methods Rectal cancer patients who underwent elective abdominoperineal resection (APR) or low anterior resection (LAR) were included from the American College of Surgeons National Surgical Quality Improvement Program database (2016)(2017)(2018).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Operative time (min). Twelve studies [11][12][13][14][15][16][17][18][19][20][21][22] reported this outcome. Random-effects models showed that the robotic approach was statistically significantly different from the laparoscopic approach and that the laparoscopic approach was superior (P < .01, MD = 23.14 [6.89, 39.40]).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Operative time (min). Twelve studies [11][12][13][14][15][16][17][18][19][20][21][22] reported this outcome. Random-effects models showed that the robotic approach was statistically significantly different from the laparoscopic approach and that the laparoscopic approach was superior (P < .01, MD = 23.14 [6.89, 39.40]).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…We hypothesize that the reason for this phenomenon may be the learning curve of robotic surgery. All studies except 3 19,20,24 reported that robotic surgery was performed by the same surgeon or the same surgical team. In studies with a relatively small sample size of the R-LAR group, the surgeon or team performing the surgery was generally at the front of the learning curve, where unskilled operations may be time-consuming, as opposed to studies with a medium or large sample size of R-LAR group, where the surgeon performing the surgery may have been on a different technical learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expected rate of APE and definitive colostomy in specialized units for the treatment of rectal cancer is around 15%, there are reports in the literature of AAP rates as high as 50% in these cases 2 . A retrospective study of 4,471 patients included in the database of the American College of Surgeon’s National Surgical Quality Improvement Program between 2016 and 2018 and conducted by Taylor et al 8 found APE rates in the US of impressive 52.2%. Lack of an adequate technique and the difficulty of performing a low colorectal or coloanal anatomosis meant that APE became adopted liberally until the end of the last century 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Many surgeons and other cancer specialists see APE as a radical procedure used to reduce the local recurrence rate. However, several papers from major centers have suggested that ideally APE should be done in no more than 15% of all cases of rectal cancer and that many of the cancers currently treated by APE, based on older concepts, could be treated by LAR using the ideas of TME with intersphincteric resection, no permanent colostomy and respect for oncological principles 1 , 2 , 4 , 5 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This minimally invasive approach provides striking benefits with regard to incisional morbidity and postoperative scarring and is likely equivalent to traditional open resection from an oncologic perspective. 1 2 Robotic surgery has recently been introduced as a new approach in achieving minimally invasive APR. Developed over the past two decades, robotic surgery offers advantages of enhanced precision, tremor elimination, motion scaling, high resolution, and three-dimensional optics.…”
Section: Introductionmentioning
confidence: 99%